JOB RESOURCE DEMAND FOR RESEARCH PERFORMANCE IN PRIVATE UNIVERSITY THROUGH WORK ENGAGEMENT - Gadzali, Silvy Sondari; Yunizar, Yunizar (Universitas Wiralodra, 2023)
The social role of lecturers as a part of the intellectual community is by doing research. This is questionable due to the low research results that show competence and work engagement in the novelty of science. The ability to understand paradigms, methodologies, and violations of a psychological breach in private tertiary institutions as an important aspect that has not received much attention. The research objective is to obtain an explanation of the ability and PCF (psychological contract fulfillment) as an antecedent for work engagement among lecturers for extra-role performance in the form of social identity theory. An explanatory survey of university permanent lecturers conducted in Kopertis IV (Coordinator of Private Universities, area IV, West Java and Banten province, Indonesia) with covariant-based SEM (Structural Equal Modeling). The analysis shows the importance of work engagement to support the social role of lecturers for the expansion and development of knowledge. Work engagement based on ability and psychological contract fulfillment have a significant influence on the extra-role of lecturers. The practical implication is to optimize the governance function of human resources (HR) to optimize abilities and encourage companies to build long-term orientation with lecturers to fulfill psychological bonds with lecturers.